Prediction of lifetime yield traits from lactation traits in graded Murrah buffaloes - KAKKAR, S; PANDER, B L; DHAKA, S S; SINGH, S (The Indian Journal of Animal Sciences, 2014)
Data on 200 graded Murrah buffaloes spreading over 31 years (1939-1969) taken from the Military Dairy farms located at Ferozpur and Jalandhar, were utilzed for the prediction of lifetime performance from lactation traits using them in sequential manner. R2 values of prediction equations increased from 42% (When first lactation traits were used) to 96% (when traits of first 4 lactations were used). It was suggested that the prediction of lifetime performance with more than 90% accuracy should include performance traits of first 4 lactations.